The Civil Society & Democracy The comparative analysis of the western and Arabic Polilical experiments - murad, Dr.Ali Abbas Murad (Dirasat in Economics and Business, 2002)
This study concentrate on the idea that "The State" is a modern form of political authority and that it is the outcome of interior factors that resulted from natural, unaffected and gradual coordination. This has happened in European countries ever since the Fifteenth Century. The most distinctive difference between "The State" and the previous forms of political authorities is the fact that the modern form of political authority relies on three essential factors: - l. Political institutions that are vocationally specialized, legal and enjoy full independence. 2. The government is chosen and sponsored by the civilian who have the right to replace it periodically and peacefully. 3. The responsibility of the government is to embody the will of the civilians, to secure their interests and fulfill their goals. These three factors cooperate together to create the democratic regime. Since this has been accomplished through the sacrifices of the civil society, it is likely to say that "The State" is the product of the civil society. Contrary to this, "The State" in the Arab countries is the product of exterior, artificial and inconsiderable factors.